Hydrogel of rosin modified nanocellulose as well as preparation method and application of hydrogel

By combining rosin with nanocellulose, a hydrogel with high mechanical properties and antibacterial effects was prepared, which solved the problem of insufficient mechanical strength and toughness of existing hydrogels and reduced the risk of toxicity of antibacterial agents.

CN119613768APending Publication Date: 2025-03-14HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608392.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing hydrogels are poor in terms of mechanical strength and toughness, difficult to withstand external forces, and some antibacterial agents are toxic, which may have adverse effects on human tissues or cells.

Method used

Rosin-modified nanocellulose hydrogel was prepared by adding rosin powder to the nanocellulose suspension, and after stirring reaction, centrifugation of ethanol and ultraviolet irradiation polymerization.

Benefits of technology

The hydrogel exhibits excellent mechanical properties, antibacterial effects and biocompatibility, has high mechanical strength, porosity, good swelling properties and low toxicity, and is suitable for antibacterial materials in the field of biomedical science.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130281430000081
    Figure BDA0005130281430000081
  • Figure BDA0005130281430000082
    Figure BDA0005130281430000082
  • Figure BDA0005130281430000091
    Figure BDA0005130281430000091
Patent Text Reader

Abstract

The invention discloses a hydrogel of rosin modified nanocellulose as well as a preparation method and application of the hydrogel, and the hydrogel is prepared by the following steps: fully stirring rosin powder (Rosin) and nanocellulose suspension (CNC) to be uniformly mixed, and centrifugally washing with ethanol to obtain a mixed solution; the preparation method comprises the following steps: dissolving an acrylamide monomer (AM), an N-N '-methylene bisacrylamide cross-linking agent (MBA) and a photoinitiator in deionized water, adding the solution into a mixed solution, and polymerizing in an ultraviolet box by adopting an ultraviolet curing polymerization method. The obtained multifunctional hydrogel forms a colloidal state through polymerization reaction at high temperature, has mechanical performance, antibacterial performance and swelling performance, and has great application potential in antibacterial composite material research in the field of biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rosin-modified nanocellulose hydrogel and a preparation method and application thereof, belonging to the technical field of polymer material synthesis. Background Art

[0002] Hydrogel is a hydrophilic polymer with a three-dimensional network structure, which has remarkable properties such as porosity and high water absorption capacity. This polymer network is interconnected by physical or chemical means, maintaining structural integrity and exhibiting excellent chemical, physical and mechanical properties. There are various methods for preparing hydrogels, including aqueous solution polymerization, inverse emulsion polymerization, etc. Hydrogels are used as filter aids in water treatment, which significantly improves the wastewater treatment effect and improves the treatment efficiency. Hydrogels are important chemical reagents in the papermaking industry, and their dispersibility is crucial to improving the quality of paper. Anionic hydrogels can be used as pulp dispersants, and low molecular weight hydrogels can be used as paper strengtheners. In the biomedical field, hydrogels are highly favored because of their properties similar to human tissues. Their controllable and adjustable structure, good biocompatibility and inertness make hydrogels widely used in medical fields such as plastic surgery, embolization, and drug sustained release.

[0003] Although rigidity and mechanical strength give nanocellulose the ability to serve as a suitable reinforcing agent for hydrogel polymer networks, nanocellulose is not suitable as a single-component gel because they are difficult to entangle with each other. The mechanical strength and toughness of single-component hydrogels are often poor. In practical applications, they may not be able to withstand certain external forces and are easily broken or damaged, thus affecting their antibacterial function. At the same time, some antibacterial agents themselves have certain toxicity. When added to hydrogels and applied to the human body, they may have adverse effects on human tissues or cells. Therefore, how to design hydrogels with good mechanical properties to ensure that they are non-toxic to the human body during use is a challenge. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a rosin-modified nanocellulose hydrogel, the second purpose of the present invention is to provide a method for preparing the rosin-modified nanocellulose hydrogel, and the third purpose of the present invention is to provide an application of the rosin-modified nanocellulose hydrogel in the preparation of antibacterial materials in the biomedical field.

[0005] Technical solution: The method for preparing a hydrogel of rosin-modified nanocellulose described in the present invention comprises the following steps:

[0006] (1) adjusting the pH of the nanocellulose (CNC) suspension, heating and stirring;

[0007] (2) adding rosin powder to the nanocellulose suspension, stirring for reaction, washing by centrifugation with ethanol, and dissolving in deionized water to obtain a mixed solution;

[0008] (3) adding monomer, crosslinking agent and photoinitiator into deionized water, adding the mixture and stirring evenly;

[0009] (4) subjecting the solution obtained in step (3) to a polymerization reaction under ultraviolet irradiation to obtain a hydrogel of rosin-modified nanocellulose.

[0010] Furthermore, in step (1), the solid content concentration of the nanocellulose suspension is 0.5-2.5%.

[0011] Furthermore, in step (1), the pH of the nanocellulose suspension is adjusted to 3.5-5.5.

[0012] Furthermore, in step (1), the temperature during heating and stirring is 110 to 140°C.

[0013] Furthermore, in step (2), the mass volume ratio of rosin to nanocellulose suspension is 15-30:100-300 g / mL.

[0014] Furthermore, in step (2), the stirring reaction temperature is 110 to 140° C., and the stirring reaction time is 20 to 30 hours.

[0015] Furthermore, in step (2), the treatment time of centrifugal washing with ethanol is 5 to 20 minutes, and the centrifugal washing with ethanol is performed 5 to 6 times.

[0016] Furthermore, in step (2), the centrifugal treatment time is 5 to 20 minutes.

[0017] Furthermore, in step (3), the monomer is acrylamide (AM).

[0018] Furthermore, in step (3), the cross-linking agent is N-N'-methylenebisacrylamide (MBA).

[0019] Furthermore, in step (3), the photoinitiator is 2-hydroxyethoxy-2-methylpropiophenone.

[0020] Furthermore, in step (3), the mass ratio of the monomer, the cross-linking agent, the photoinitiator and the deionized water is 4.96-6.96: 0.00835-0.0334: 0.0894: 3-7.

[0021] Furthermore, in step (4), the power of ultraviolet irradiation is 1000 to 3000W.

[0022] Furthermore, in step (4), the polymerization reaction time is 10 to 25 minutes.

[0023] The hydrogel of rosin-modified nanocellulose is obtained by the preparation method of the invention.

[0024] The invention discloses an application of the rosin-modified nanocellulose hydrogel in the preparation of antibacterial materials in the biomedical field.

[0025] The rosin used in the present invention has a large rigid skeleton structure, which brings excellent stability to its molecular conformation and also produces unique intermolecular interactions. In the process of molecular aggregation, these rigid groups can act as a solid framework and support in the self-assembled structure, which can reduce the repulsive force between particles and promote gel formation, not only retaining the mechanical strength of nanocellulose, but also combining the antibacterial ability of rosin, thereby forming a more potent antibacterial substance. Rosin-modified nanocellulose hydrogel has excellent mechanical stability, shear-thinning behavior, adjustable mechanical properties, high water retention capacity, controllable morphology, high biocompatibility and biodegradability, so that its application in the fields of cosmetics, drug delivery, tissue engineering and food industry has received extensive attention. Compared with traditional hydrogels, rosin-modified nanocellulose hydrogel has higher bioavailability and lower toxicity, and is an ideal antibacterial material.

[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0027] (1) The multifunctional hydrogel provided by the present invention exhibits excellent mechanical properties, with a mechanical strength of up to 1379%. It also has excellent compression properties and good recoverability after compression deformation. This property has wide applications in medical fields such as plastic surgery, embolization, and drug sustained release.

[0028] (2) The multifunctional hydrogel provided by the present invention is highly porous, providing abundant internal space for the hydrogel, which can increase the water content of the hydrogel and plays an important role in biomedicine and antibacterial materials.

[0029] (3) The multifunctional hydrogel provided by the present invention has good biocompatibility and has good antibacterial effect on Staphylococcus aureus and Escherichia coli, etc., and has great application potential in the biomedical field.

[0030] (4) The multifunctional hydrogel provided by the present invention has good swelling properties, with a swelling rate of up to 603.421%, which can simulate the natural tissue environment and promote wound healing.

[0031] (5) The method of the present invention has a simple preparation process, low cost, and recyclable raw materials. It can efficiently prepare antibacterial hydrogels and is suitable for large-scale commercial production. It not only improves production efficiency but also optimizes cost-effectiveness and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the infrared spectra of Rosin@CNC and CNC hydrogel prepared in Example 1;

[0033] Figure 2 is a scanning electron microscope image of the PAM / Rosin@CNC hydrogel, CNC and Rosin@CNC prepared in Example 1;

[0034] Figure 3 is the X-ray diffraction pattern of PAM / Rosin@CNC, Rosin@CNC and CNC prepared in Example 1 and PAM / CNC hydrogel prepared in Comparative Example 1;

[0035] Figure 4 Schematic diagram of stretching, twisting and knotting of the antibacterial multifunctional hydrogel of rosin-modified nanocellulose prepared in Example 1;

[0036] Figure 5 Schematic diagram of skin fitting of rosin-modified nanocellulose antibacterial multifunctional hydrogel prepared in Example;

[0037] Figure 6 It is a graph showing the mechanical properties of the antibacterial multifunctional hydrogel of rosin-modified nanocellulose prepared in Example 1 and Example 2;

[0038] Figure 7 The toughness and elastic modulus graphs of the hydrogels obtained for Examples 1-4 and Comparative Example 1.

[0039] Figure 8 Rosin@CNC with 200% strain of hydrogel under the optimal conditions in Example 4 0.3125 Multi-cycle stretching diagram of hydrogel;

[0040] Fig. 9 The antibacterial results of the hydrogels prepared in Example 1 and Comparative Examples 1-2 on Escherichia coli BL21 and Staphylococcus aureus SD are shown;

[0041] Fig.10 This is a graph of the swelling degree and conductive properties of the rosin-modified antibacterial multifunctional hydrogel of nanocellulose prepared in Example 1 or Example 6. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0043] In the following examples of the present invention, the nanocellulose used was purchased from Qingdao Keming New Energy Technology Co., Ltd., and rosin, acrylamide, and N,N'-methylenebisacrylamide were all purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0044] Example 1

[0045] 1. Preparation of Rosin@CNC solution:

[0046] 200 mL of CNC suspension (solid content of CNC suspension is 1%) was added to a three-necked flask, and the pH of the solution was adjusted to 4.0 with 5% HCl. The flask was equipped with a condenser and connected to a closed water distillation system. The three-necked flask containing the CNC suspension was stirred in an oil bath with a magnetic stirrer at a speed of 1200 rpm and heated to 130°C. Then 20 g of rosin powder (10 / 1 CNC, wt / wt) was added and the reaction was stirred continuously for 24 h under a nitrogen environment. After the reaction, rosin-modified CNC was obtained, which was then washed with anhydrous ethanol and centrifuged in a desktop high-speed microcentrifuge at a speed of 10,000 rpm at 4°C for 5 times, each centrifugation time was 10 min, and the excess rosin was removed to obtain Rosin@CNC, which was then redissolved in 200 mL of deionized water with an equal mass of deionized water to obtain Rosin@CNC solution.

[0047] 2. Weigh 4.96 g of AM, 8.35 mg of MBA crosslinker, 0.0894 g of photoinitiator 2-hydroxyethoxy-2-methylpropiophenone, 3 g of deionized water and 4 mL of Rosin@CNC solution on a magnetic stirrer and mix them evenly. Add deionized water to make the total solution system 16 mL, that is, the mass fraction of Rosin@CNC solution relative to the total system is 0.25 wt %. Pour the PAM / Rosin@CNC solution into a mold (the mold is a 100×1 with a thickness of 2 mm). 00mm transparent glass plate), covered with a 2mm thick hollow square silicone sheet, and then covered with a 5mm thick 100×100mm transparent glass plate. During the pouring process, bubbles should be avoided as much as possible, and then the mold was fixed with dovetail clips on all sides and placed in a 1.6kW UV box for UV curing polymerization reaction. The polymerization time was 20min. Pay attention to the placement method when placing it to ensure that the glue is heated and gelled evenly, and the rosin-modified nanocellulose antibacterial multifunctional hydrogel PAM / Rosin@CNC was obtained.

[0048] The infrared spectrum analysis of Rosin@CNC and CNC obtained in Example 1 was performed, and the results were as follows: Figure 1 As shown. Figure 1 As shown in the figure, after chemical modification of rosin, the -1 A new band was observed at 2656 cm-1, which may be due to the C=O vibration of the ester functional group caused by the reaction of rosin carboxylic acid with the hydroxyl functional group of cellulose. -1No bands associated with free rosin were observed at 3300 cm-1, confirming that all excess rosin not bound to CNCs had been completely washed away during the previous centrifugation washing step. Although the esterification reaction represents the replacement of a portion of the more polar hydroxyl groups with less polar ester groups, no bands at 3300 cm-1 were observed. -1 The intensity of the band associated with the vibration of OH groups decreased significantly, which may be because the esterification reaction mainly occurred on the more accessible hydroxyl groups on the CNC surface.

[0049] The multifunctional antibacterial hydrogels PAM / Rosin@CNC, CNC and Rosin@CNC modified with rosin obtained in this example were analyzed by scanning electron microscopy. Figure 2 shown. Figure 2 Figure 1 is a scanning electron microscope image of the PAM / Rosin@CNC hydrogel, CNC and Rosin@CNC prepared in Example 1, wherein A is CNC, B is Rosin@CNC, and C is PAM / Rosin@CNC. Figure 2 It can be seen that the Rosin@CNC hydrogel structure is highly porous, which is similar to the mesh interweaving in three-dimensional space, providing rich internal space for the hydrogel and an important practical basis for its future application prospects.

[0050] The Rosin@CNC solution and CNC suspension obtained in this example were subjected to X-ray diffraction analysis, and the results were as follows: Figure 3 shown.

[0051] The multifunctional PAM / Rosin@CNC hydrogel with antibacterial properties modified by rosin nanocellulose obtained in this example was stretched, twisted and knotted. Figure 4 As shown. Figure 4 It can be seen that the PAM / Rosin@CNC hydrogel prepared in this example has excellent properties of stretching, twisting, and knotting while maintaining the original morphology.

[0052] The multifunctional hydrogel of rosin-modified nanocellulose antibacterial obtained in this example was applied to the skin, and the results were as follows: Figure 5 As shown. Figure 5 It can be seen that the PAM / Rosin@CNC hydrogel prepared in this example can have good adhesion without any adhesion residue when peeled off, which provides a prerequisite for its application in the medical field.

[0053] Comparative Example 1 Preparation of PAM / CNC hydrogel

[0054] The preparation of PAM / CNC hydrogel is the same as that in Example 1, except that rosin modification is not used, specifically as follows: 4.96 g of AM, 8.35 mg of MBA cross-linking agent, 0.0894 g of photoinitiator 2-hydroxyethoxy-2-methylpropiophenone and 3 g of deionized water are weighed and mixed evenly with 4 mL of CNC solution on a magnetic stirrer, deionized water is added to make the total solution system 16 mL, the mixed solution is poured into a mold, and then the mold is fixed with a dovetail clamp on all sides, and placed in a 1.6 kW UV box for UV curing polymerization reaction, the polymerization time is 20 min, and the PAM / CNC hydrogel is obtained.

[0055] The PAM / CNC hydrogel prepared in this comparative example was subjected to X-ray diffraction analysis, and the results were as follows: Figure 3 shown.

[0056] Figure 3 The X-ray diffraction patterns of PAM / Rosin@CNC, Rosin@CNC and CNC prepared in Example 1 and PAM / CNC hydrogel prepared in Comparative Example 1, wherein A is the X-ray diffraction pattern of Rosin@CNC and CNC, and B is the X-ray diffraction pattern of PAM / Rosin@CNC hydrogel and PAM / CNC hydrogel. Figure 3 As can be seen in Figure A, both CNC and Rosin@CNC samples show typical diffraction peaks at 2θ=15°, 23° and 35°. Relative to the cellulose crystal structure, the crystallinity index of pure CNC is calculated to be 75.2%, and the crystallinity index of Rosin@CNC is 77.7%, which indicates that long-term (24h) chemical modification under high temperature (130℃) and acidic conditions (pH 4.0) does not change the structure and crystallinity index of cellulose, but higher temperature may destroy PAM / Rosin@CNC. Figure 3 Figure B shows that PAM / CNC hydrogel has obvious broad peaks between 2θ=10° and 2θ=45°, indicating that its crystallinity is extremely poor; PAM / Rosin@CNC hydrogel has multiple obvious peaks at 2θ=13°~29°, indicating that PAM / Rosin@CNC hydrogel has good crystallinity. The crystallinity of Rosin@CNC hydrogel is 70.43% calculated by the crystallinity calculation formula, so Rosin@CNC hydrogel has better crystallization effect.

[0057] Comparative Example 2 Preparation of PAM / CNC / Rosin hydrogel

[0058] The preparation of PAM / CNC / Rosin hydrogel is the same as that in Example 1, except that the addition method of rosin is different, and physical mixing is adopted, that is, the process of stirring and reacting without heating is adopted, which is as follows: 20g of rosin powder is dissolved in 50-100ml of anhydrous ethanol solution, stirred by a magnetic stirrer until the rosin is dissolved, and then mixed with the CNC suspension to obtain a CNC / Rosin solution by physical mixing without modification, that is, a Rosin / CNC solution. Finally, 4.96g of AM, 8.35mg of MBA crosslinker, 0.0894g of photoinitiator and 3g of deionized water and 4mL of mixed solution are weighed and stirred evenly on a magnetic stirrer, deionized water is added to make the total system of the solution 16mL, the newly mixed solution is poured into a mold, and then the mold is fixed around with a dovetail clip, and placed in a 1.6kW UV box for UV curing polymerization reaction, and the polymerization time is 20min to obtain PAM / CNC / Rosin hydrogel.

[0059] Example 2

[0060] The preparation process and steps are basically the same as those in Example 1, except that the amount of Rosin@CNC solution added is carried out in five gradients of 3 mL, 5 mL, 6 mL, and 7 mL. Before gelation, the total solution system is 16 mL, that is, the mass fraction of Rosin@CNC solution relative to the total system is 0.1875 wt%, 0.3125 wt%, 0.375 wt%, and 0.4375 wt%, to obtain multifunctional hydrogels with different concentrations of composite rosin-modified nanocellulose antibacterial properties.

[0061] The tensile properties of the multifunctional hydrogel of composite rosin-modified nanocellulose antibacterial obtained in this example and example 1 were tested, and the results are shown in Figure 6 A, by Figure 6 As shown in A, when the concentration of Rosin@CNC is 0.3125wt%, the elongation reaches the maximum value. The toughness and elastic modulus of the hydrogels obtained in Examples 1-4 and Comparative Example 1 were calculated using origin software. The results are shown in Figure 7 . Figure 7 The toughness and elastic modulus of the hydrogels obtained for Examples 1-4 and Comparative Example 1 are shown in FIG. Figure 7 It can be seen that according to the initial slope of the stress-strain curve in the linear part, it can be concluded that the hydrogels prepared in Examples 1-4 all have an excellent toughness of 50 kJ / m3.

[0062] Example 3

[0063] The preparation process steps are basically the same as those in Example 1, except that the concentration of Rosin@CNC is 0.3125wt%, and the addition amount of AM is changed to 4.96, 5.46g, 5.96g, 6.46g, and 6.96g, respectively, to obtain 5 groups of composite rosin-modified nanocellulose antibacterial multifunctional hydrogels.

[0064] The tensile properties of the multifunctional hydrogel of composite rosin-modified nanocellulose antibacterial obtained in this example were tested, and the results are shown in Figure 6 Middle B, by Figure 6 As can be seen in Figure B, when the concentration of Rosin@CNC is 0.3125wt% and the amount of AM added is 5.96g, the elongation reaches the maximum value.

[0065] Example 4

[0066] The preparation process steps are basically the same as those in Example 1, except that the concentration of Rosin@CNC is 0.3125wt%, the addition amount of AM is changed to 5.96g, and the addition amount of MBA is changed to 8.35mg, 12.53mg, 16.7mg, 20.88mg, 25.05mg, and 33.4mg, respectively, to obtain 6 groups of composite rosin-modified nanocellulose antibacterial multifunctional hydrogels.

[0067] The tensile properties of the multifunctional hydrogel of composite rosin-modified nanocellulose antibacterial obtained in this example were tested, and the results are shown in Figure 6 Middle B. By Figure 6 As can be seen in B, Figure 6 As shown in Figure C, when the addition amount of MBA is 20.88 mg, the elongation reaches the maximum value. Therefore, it can be seen that the mechanical properties are best when the concentration of Rosin@CNC is 0.3125wt%, AM is 5.96g, and MBA is 20.88mg.

[0068] The hydrogel PAM / Rosin@CNC obtained under the optimal conditions of this embodiment, that is, the concentration of Rosin@CNC is 0.3125wt%, the AM is 5.96g, and the MBA is 20.88mg, was subjected to a continuous tensile test. The results are as follows: Figure 8 shown. Figure 8 Rosin@CNC with 200% strain of hydrogel under the optimal conditions in Example 4 0.3125 The hydrogel multi-cycle stretching diagram is Figure 8 It can be seen that the hydrogel showed excellent elasticity and fatigue resistance in the cyclic test of 10 consecutive stretching to 200%. In the continuous stretching cycle, the multiple stretching curves of PAM / Rosin@CNC hydrogel almost overlapped, which strongly proved the excellent fatigue resistance of PAM / Rosin@CNC hydrogel.

[0069] Example 5

[0070] The antibacterial properties of the CNC solution, Rosin@CNC solution (referred to as Rosin@CNC-0.25 in this example), the multifunctional hydrogel PAM / Rosin@CNC (referred to as PAM / CNC@Rosin-0.25 in this example) prepared in Example 1, the hydrogel PAM / CNC prepared in Comparative Example 1, and the CNC / Rosin solution and hydrogel AM / CNC / Rosin prepared in Comparative Example 2 were tested according to the following steps: single colonies of Escherichia coli BL21 (purchased from Novagan, USA) and Staphylococcus aureus SD (purchased from Novagan, USA) streaked on a plate were selected and inoculated into a test tube containing 5 mL of LB liquid culture medium, and cultured at 37°C and 180 rpm for 12 h. The OD of the bacterial solution was set to 0.0447 W / cm2. 600 After adjusting to 0.6, 50 μL of bacterial solution was spread on LB solid culture medium. One group took 10 μL of CNC solution, Rosin@CNC-0.25 solution, and CNC / Rosin solution and spotted them on sterilized filter paper with a diameter of 5.5 mm. The other group used a sterilized cutter to cut the above three gel blocks (PAM / CNC@Rosin-0.25 hydrogel, PAM / CNC hydrogel, and PAM / CNC / Rosin hydrogel), and placed them in an incubator at 37°C for 12 hours to observe the shape and size of the inhibition zone. The results are shown in Figure 2. Fig. 9 And as shown in Table 1.

[0071] Fig. 9 The antibacterial results of the hydrogel prepared in Example 1 and Comparative Examples 1-2 on Escherichia coli BL21 and Staphylococcus aureus SD are shown, wherein AB is the antibacterial effect of Escherichia coli film, DE is the antibacterial effect of Staphylococcus aureus film, C is the antibacterial effect of Escherichia coli film co-culture (the left side is the result just after culture, and the right side is the result after culture), and D is the antibacterial effect of Staphylococcus aureus co-culture (the left side is the result just after culture, and the right side is the result after culture).

[0072] Table 1 Comparison of hydrogel antibacterial zone size

[0073]

[0074] a: physically mixed Rosin and CNC; b: chemically modified CNC with Rosin; PAM: polyacrylamide; the data in the table are the difference between the outer diameter and the inner diameter of the inhibition zone.

[0075] Depend on Fig. 9(A, B, D and E) and Table 1 show that the size and shape of the inhibition zone show that Rosin@CNC has a significant antibacterial effect compared with pure CNC. Fig. 9 (C and F) The bacterial solution in the test tube was clear, showing a significant antibacterial effect.

[0076] Example 6

[0077] The swelling degree and electrical conductivity of the rosin-modified nanocellulose antibacterial multifunctional hydrogel prepared in Example 1-2 were tested according to the following steps:

[0078] Swelling degree determination: 1 g of hydrogel was placed in a freeze dryer for freeze drying, and then the freeze-dried hydrogel was immersed in 5 g of deionized water until swelling equilibrium was reached. The swelling ratio (SR) formula was used to calculate the swelling performance of the hydrogel. The calculation formula is:

[0079]

[0080] Where: Ws is the mass of the hydrogel at swelling equilibrium, in g; Wd is the mass of the freeze-dried hydrogel, in g.

[0081] Conductivity measurement: prepare a film with a size of about 5×5mm to 10×10mm, a thickness of less than 2mm, and a flat and clean surface. The standard unit of conductivity is S / m, that is, when a current of 1A passes through the cross section of an object and generates a voltage difference of 1V on the cross section, the conductivity of the object is 1S. In order to quantitatively calculate the conductivity, the following formula is used for calculation:

[0082]

[0083] Where: R is the resistance, A is the cross-sectional area of ​​the hydrogel sample. Therefore, the conductivity essentially describes the conductivity of a sample with a length of 1m and a cross-sectional area of ​​1m. 2 The conductivity of a substance, or a volume of 1m 3 The conductivity of a conductor.

[0084] The swelling and conductivity results are shown in Fig.10 As shown, Fig.10 The graphs are the swelling degree and conductivity performance of the hydrogels prepared in Example 1-2, wherein A is the swelling rate graph of the PAM / Rosin@CNC hydrogels obtained with different Rosin@CNC solution dosages, and B is the conductivity graph of the PAM / Rosin@CNC hydrogels obtained with different Rosin@CNC solution dosages. Fig.10It can be seen from Figure A that the hydrogel under the condition of PAM / Rosin@CNC-0.25wt% has a swelling rate of 603.42% after 108h, showing excellent swelling performance. Therefore, through systematic research and regulation, the swelling performance of hydrogel can be effectively improved. Fig.10 As shown in Figure B, the conductivity of the three groups of Rosin@CNC-0.25 (hydrogel obtained by using 0.25wt% of Rosin@CNC solution), Rosin@CNC-0.3125 (0.3125wt% of Rosin@CNC solution), and Rosin@CNC-0.375 (0.375wt% of Rosin@CNC solution) are 0.0217mS / cm, 0.0257mS / cm, and 0.025mS / cm, respectively. It can be seen that different addition amounts of Rosin@CNC solution have almost no effect on the conductivity of the finished hydrogel. By adding conductive polymers (such as polyaniline, metal particles, polysaccharides and proteins, etc.), conductive nano-ions and other substances, hydrogels can be given good conductive properties, thereby overcoming their limitations in use.

[0085] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing rosin-modified nanocellulose hydrogel, characterized in that: The following steps are involved: (1) adjusting the pH of the nanocellulose suspension, heating and stirring; (2) adding rosin powder to the nanocellulose suspension, stirring for reaction, washing by centrifugation with ethanol, and dissolving in deionized water to obtain a mixed solution; (3) adding monomer, crosslinking agent and photoinitiator into deionized water, adding the mixture and stirring evenly; (4) subjecting the solution obtained in step (3) to a polymerization reaction under ultraviolet irradiation to obtain a hydrogel of rosin-modified nanocellulose.

2. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (1), the solid content concentration of the nanocellulose suspension is 0.5-2.5%.

3. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (1), the pH of the nanocellulose suspension is adjusted to 3.5-5.5, and the temperature during heating and stirring is 110-140°C.

4. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (2), the mass volume ratio of rosin to nanocellulose suspension is 15-30:100-300 g / mL.

5. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (2), the stirring reaction time is 20-30 hours, the treatment time of centrifugal washing with ethanol is 5-20 minutes, and the centrifugal washing with ethanol is performed 5-6 times.

6. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (3), the monomer is acrylamide, the cross-linking agent is N-N'-methylenebisacrylamide, and the photoinitiator is 2-hydroxyethoxy-2-methylpropiophenone.

7. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (3), the mass ratio of monomer, cross-linking agent, photoinitiator and deionized water is 4.96-6.96: 0.00835-0.0334: 0.0894: 3-7.

8. The method for preparing the hydrogel of rosin-modified nanocellulose according to claim 1, characterized in that: In step (4), the power of ultraviolet irradiation is 1000-3000W, and the polymerization reaction time is 10-25min.

9. The hydrogel of rosin-modified nanocellulose obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the rosin-modified nanocellulose hydrogel according to claim 8 in the preparation of antibacterial materials in the biomedical field.